Analisis kepemimpinan kepala sekolah dalam meningkatkan kualitas pembelajaran - Sumardi Sumardi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
Quality learning is part of the performance of teachers who have high competence, both pedagogic, professional, personality, and social competencies. In order for the teacher's performance to be good, in learning there needs to be supervision from the principal. Teaching quality Buddhist education cannot be separated from the role of the principal in monitoring both the implementation of the learning process and administration. This research was conducted to find out how good the principal's leadership is in improving the quality of teaching Buddhist education and how the principal's leadership style can improve the quality of teaching Buddhist education at the elementary school level in Jambi City. This study uses a qualitative method with a phenomenological approach, namely looking closely and in depth by visiting schools with Buddhist education teachers descriptively and through interviews with school principals and Buddhist education teachers. The results showed that the principal's leadership through the supervision of learning and administration greatly influenced the quality of teaching Buddhist education in elementary schools in Jambi City.